“Linguistic Evidence on Issues of Disagreement Between the Kufans and The Basrans” - Al mashaqaba, Fudda suliman muslim (Journal of Ecohumanism, 2024)
This research explores linguistic evidence in matters of scholarly disputes, focusing on both traditional (transmitted) and logical (reasoned and analogical) evidence. Using Ibn Al-Anbari’s work as a primary source, the study examines six specific disputes, analyzing various opinions and evaluating their validity. The research also draws on the Quran as the fundamental reference for principles, discussing the theory of causation and different grammatical rules that have been contested. The emphasis is on the type and direction of the evidence rather than the specific disputes.The study is organized into an introduction, which covers the reasons for choosing the topic, previous studies, research problems, and methodology. The first chapter delves into the disputes over transmitted and rational evidence, defining linguistic evidence, comparing the perspectives of Basra and Kufa scholars, and examining specific issues such as the causation in the predicate after the negative particle "ما" and the prohibition of declension in poetic necessity.